ผลของโปรแกรมการส่งเสริมการดูแลร่วมกันต่อการดูแลร่วมกันของผู้ป่วย และครอบครัว ภาวะโภชนาการ และการติดเชื้อที่แผลช่องสายออกในผู้ป่วยล้างไตทางหน้าท้องแบบต่อเนื่อง - Pairojkittrakul, Sasipim; Harnirattisai, Teeranut; Thitiarchakul, Supachai (Nursing Research and Innovation Journal, 2015)
This study is of a quasi-experimental research design aimed to evaluate the effects of a Shared care promoting program of patients and families, nutritional status and exit site infection among CAPD patients. The experimental group received the shared care promoting program, design based on Sebern’s shared care model by the investigator, whereas the control group received usual care by the nursing staff. The instruments used were a demographic questionnaire, a Shared Care Instrument , Serum albumin, Nutrition Alert Form and Exit site assessment form a shared care plan and a shared care handbook for CAPD patients. Data were analyzed by using descriptive statistics, Independent Sample t-test, Paired Sample t-test, Repeated Measure ANOVA test. The findings showed that the experimental group had a higher mean score of shared care in the part of communication, decision making and reciprocity and serum albumin level after the shared care promoting program and lower mean score of nutrition alert than those of the control group and before starting the program . For exit site infection, the mean scores of the exit site infection after receiving shared care program is no different of the control group. However both of them had significantly decrease the mean score of exit site infection. These resulted demonstrated that a shared care promoting program can increase shared care among the patients and families, serum albumin level and decrease nutrition alert score. Nurse and health care teams can apply this program to promote shared care between patients and their families in order to have good nutrition and the prevention of exit site infection among CAPD patients.